Economics of high-tensile steel in ship hulls - 267125 Loseth, Robert; Sekkesaeter, Geir; Valsgard, Sverre; International Symposium on the Practical Design of Ships and Mobile Units (5th : 1992 : University of Newcastle-upon-Tyne, UK)
19